Determining response and recurrence in pediatric B‐cell lymphomas of the bone. Issue 8 (20th March 2013) - Borst, Alexandra J.; States, Lisa J.; Reilly, Anne F.; Rheingold, Susan R.
Abstract Background Primary lymphomas of the bone are rare in children, but have an excellent response to therapy. Evaluating patients for remission and recurrence can be challenging given the difficulties of distinguishing healing bone from residual tumor on imaging. A review of imaging in patients treated for primary bone lymphoma (PBL) in one center was performed in an effort to determine best practice. Methods Twelve cases of PBL diagnosed and treated from 2000 to 2011 at the Children's Hospital of Philadelphia were identified. Information about presentation, histology, imaging, treatment, and outcomes was collected. Results There were no recurrences of the primary bone tumor after therapy. One patient developed therapy‐related AML. Although PET‐avid lesions usually fell below a SUVmax of 3 within 3 months, low‐level SUVmax lesions often remained up to 12 months post‐therapy. At no point during therapy did radiographs, MRI, bone scans or CT of bones normalize, most remaining abnormal for several months to years. Patients were exposed to significant ionizing radiation, with estimated levels ranging from 9.5 to 183.1 mSv per patient. Over 10% of scans had incidental findings, which led to 17 extra imaging studies and 4 biopsies, but no clinically significant outcomes. Conclusions In our cohort, frequent imaging did not affect or improve outcome. Due to the low risk of relapse and high rate of repeated imaging for incidental findings, minimization of post‐therapy imaging should be considered. This modification in practice will significantly reduce radiation exposure, as well as potentially decrease parent and patient anxiety. Pediatr Blood Cancer 2013;601281‐1286. © 2013 Wiley Periodicals, Inc.